Real-World Medical Cost Avoidance When New Oral Anticoagulants are Used Versus Warfarin for Venous Thromboembolism in the United States. (January 2016) - Amin, Alpesh; Bruno, Amanda; Trocio, Jeffrey; Lin, Jay; Lingohr-Smith, Melissa
Objective: Real-world medical cost avoidances from a US payer perspective were estimated when new oral anticoagulants (NOACs) are used instead of warfarin for the treatment of patients with venous thromboembolism (VTE). Methods: Reductions in real-world event rates of recurrent VTE and MB were obtained by applying rate reductions from the NOACs versus warfarin trials to the Worcester population. Incremental annual medical costs among patients with VTE and MB from a US payer perspective were obtained from the literature or claims databases. Differences in total medical costs for patients treated with NOACs versus warfarin were then estimated. Univariate and Monte Carlo sensitivity analyses were additionally carried out. Results: The annual total medical cost avoidances versus warfarin were greatest for VTE patients treated with apixaban (−US4440 per patient-year [ppy]), followed by those treated with rivaroxaban (−US2971 ppy), edoxaban (−US1957 ppy), and dabigatran (−US572 ppy). The medical cost avoidances remained consistent under sensitivity analyses. Conclusion: Based on real-world data, when any of the evaluated NOACs are used instead of warfarin for treatment of patients with acute VTE, annual medical costs are reduced. Of the NOACs, apixaban has the greatest real-world medical cost avoidance, as its use is associated with substantial reductions in both VTE and MB event rates.